How many hours do you have to work to be integrated? Full time and part time employment of native and ethnic minority women in the Netherlands - Pieter Bevelander; Sandra Groeneveld (Institute for the Study of Labor (IZA), 2007)
Labor market participation is a central factor in the economic integration of migrants in their host country. Labor market integration of ethnic minority women is of special interest, as they may experience a double disadvantage: both as a woman and as a migrant. Since the late nineties this presumed double disadvantage has become more and more the focus of both Dutch integration and Dutch emancipation policy. To test several assumptions underlying Dutch policy this paper focuses on the employment patterns of ethnic minority and native women in the Netherlands. In particular, we analyze to what extent labor market participation of different groups of women and the hours they work are influenced by human capital and household characteristics. Our results show some remarkable differences in employment patterns between native Dutch and ethnic minority women. Controlling for educational level, partnership and the presence of children, native Dutch women are working more often in part time jobs than Mediterranean and Caribbean women. For all women the educational level is an important determinant of employment and the number of hours worked. Whereas the number of children influences both the employment decision and the number of hours worked of native Dutch women, for Mediterranean and Caribbean women there is only an effect of the number of children on the odds of having a full time job.
urn:nbn:de:101:1-2008041465
Keywords: 330; Frauenerwerbstätigkeit; Migranten; Ethnische Gruppe; Arbeitsverhältnis; Teilzeitarbeit; Berufliche Integration; Niederlande